Modelo conceitual para a aplicação de FMEA de processo na indústria automotiva - Aguiar, Dimas Campos de [UNESP] (2016)
In recent years it has been possible to note a considerable growth in the number of companies and people who use the Failure Mode and Effects Analysis, or FMEA, in process analysis. However, in its execution there are uncertainty situations, making possible to promote different types of information, raising questions whether the assessments are really complete. This study aims to define a conceptual model for Process FMEA application, reducing variations in interpretations, scoring and decisions criteria. From a theoretical framework, a structure for FMEA construction is identified, where those development activities are classified as qualitative, quantitative and corrective, according to the type of analysis of the evaluations. A specific study is developed for each category of evaluation. A case study in FMEA application associated with the concepts of process approach is done regarding qualitative analysis; a literature review on scoring FMEA criteria is done regarding quantitative analysis; and a survey on the rules used for recommending actions in Process FMEA is done regarding corrective analysis. As output, a proposal focused on the elimination of irregularities in the implementation of FMEA is done, filling a gap between theory and practice.